2020
DOI: 10.3390/prosthesis2010004
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Operative Modeling of Transcatheter Mitral Valve Replacement in a Surgical Heart Valve Bioprosthesis

Abstract: Obstruction of the left ventricular outflow tract (LVOT) is a common complication of transcatheter mitral valve replacement (TMVR). This procedure can determine an elongation of an LVOT (namely, the neo-LVOT), ultimately portending hemodynamic impairment and patient death. This study aimed to understand the biomechanical implications of LVOT obstruction in a patient who underwent TMVR using a transcatheter heart valve (THV) to repair a failed bioprosthetic heart valve. We first reconstructed the heart anatomy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
(37 reference statements)
0
1
0
Order By: Relevance
“…In the case of edge-to-edge mitral valve repair, simulations of the surgical procedure were compared to echocardiography, revealing that the stress in the leaflets after the edge-to-edge suture was reduced [36]. In previous studies, we demonstrated the feasibility of transcatheter mitral valve replacement in the setting of failed annuloplasty band ring [37], surgical bioprosthesis [38], and massive mitral valve calcifications [39]. In computational studies of the MitraClip, Morgan and collaborators concluded that an uneven MitraClip position led to low anterior and posterior leaflet stress with respect to the model with leaflet prolapse and no clip [40].…”
mentioning
confidence: 99%
“…In the case of edge-to-edge mitral valve repair, simulations of the surgical procedure were compared to echocardiography, revealing that the stress in the leaflets after the edge-to-edge suture was reduced [36]. In previous studies, we demonstrated the feasibility of transcatheter mitral valve replacement in the setting of failed annuloplasty band ring [37], surgical bioprosthesis [38], and massive mitral valve calcifications [39]. In computational studies of the MitraClip, Morgan and collaborators concluded that an uneven MitraClip position led to low anterior and posterior leaflet stress with respect to the model with leaflet prolapse and no clip [40].…”
mentioning
confidence: 99%